Pengembangan Media Pembelajaran “Pop-Up Book” Pada Mata Pelajaran Matematika Materi Bangun Ruang Di Kelas VI - Khasmi, Charistiya Aja; Sari, Kanthi Pamungkas (UNIB Press, 2025)
In grade 6 MIM 01 Tempuran they do not quickly understand the mastery of building space material in mathematics subjects. This happens because the 6th grade teacher still uses conventional learning methods, namely lectures, resulting in students taking a long time to understand the material and even the material taught is more than the target that should be determined. The research method used is classroom action research aimed at understanding the improvement in the actions that researchers have taken on the problems that occur. This action research was conducted in 2 cycles, namely cycle 1 and cycle 2. The object of the action is the 6th grade students of MI Muhammadiyah 01 Tempuran and the subject of the action is the 6th grade teacher of MI Muhammadiyah 01 Tempuran. The improvement can be seen from the results of the pre-test in cycle 1, there are still students whose scores are below 70. After the action in cycle 1 was then carried out a post-test, the results showed that the students' scores had increased but not all students with scores above 70. Then for this reason the researcher continued the action in cycle 2 with additional treatment, namely students playing a more active role in learning and taking a pre-test and the results had improved from the previous post-test. And after additional treatment is given, it can be seen again the results of student scores with a post-test with most students scoring above 70.